2020
DOI: 10.1097/aci.0000000000000712
|View full text |Cite
|
Sign up to set email alerts
|

Cellular interactions in aspirin-exacerbated respiratory disease

Abstract: Purpose of review The purpose of this review is to summarize the complex cellular interactions of aspirin-exacerbated respiratory disease (AERD) and how these interactions promote pathogenic mechanisms of AERD. Recent findings In addition to characteristic changes in eicosanoid levels, recent studies have identified increases in alarmin cytokines (IL-33, thymic stromal lymphopoietin) as well as activated innate lymphoid and plasma cell populations in sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Eosinophils, abundant in nasal polyps, bronchial mucosa, and peripheral blood, produce PGD 2 and are attracted to PGD 2 by chemotaxis ( 40 ). Choi et al found that eosinophils interact with epithelial cells through surfactant protein D, and may mediate smooth muscle remodeling, a clinical feature of AERD ( 41 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eosinophils, abundant in nasal polyps, bronchial mucosa, and peripheral blood, produce PGD 2 and are attracted to PGD 2 by chemotaxis ( 40 ). Choi et al found that eosinophils interact with epithelial cells through surfactant protein D, and may mediate smooth muscle remodeling, a clinical feature of AERD ( 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…The three first mentioned may stimulate plasma cells to produce IgE and IgG4. IL-5 also promotes recruitment, survival and activation of eosinophils and IL-9 may increase the amount of mast cells recruited to the tissue ( 40 ). Several prostaglandins also regulate ILC2 function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Leukotrienes can cause the accumulation of large numbers of leucocytes and other inflammatory cells, which can lead to contraction of airway smooth muscle, increased vascular permeability and mucus secretion. 37,38 Some other inflammatory mediators also activate CysLTs. 39 Furthermore, CysLTs interact with other inflammatory mediators to amplify the cascade of inflammatory responses and promote disease progression.…”
Section: Food Function Papermentioning
confidence: 99%
“… 2 6 AERD pathogenesis involves interactions with several immune cellular players, including mast cells, eosinophils, basophils, T cells, and group 2 innate lymphoid cells (ILC2s). 7 , 8 CysLTs contribute to the release of epithelial IL-33, which can activate mast cells to induce release of PGD 2 . 9 PGD 2 can, in turn, activate eosinophils, basophils, T H 2 cells, and ILC2s by binding to chemoattractant receptor–homologous molecules expressed on T H 2 cells (CRTH2).…”
Section: Introductionmentioning
confidence: 99%